Analysis on Characteristics of Surrounding Rocks of Roadway and Bearing Structure Based on Stress Regulation. (22nd March 2021) - Zhang, Ruofei; Zhao, Guangming; Meng, Xiangrui; Sun, Jian; Xu, Wensong; Li, Yingming; Liu, Zenghui; Kao, Siming
Abstract : To address the prominent status of great deformation and difficult maintenance of the roadway under high stresses, this study investigated the mechanical characteristics of surrounding rocks and bearing structural stability in a roadway under adjustment and redistribution of stresses through theoretical analysis, numerical simulation, and engineering field test. Stability forms of the bearing structure of roadway surrounding rocks were analyzed by using the axis-changing theory from the perspectives of surrounding rock, mechanical properties of roadways, surrounding rock stress distribution, and mechanical mechanism of the bearing structure. It is suggested that the surrounding rock stress distribution state is improved and the bearing structure is optimized through unloading and reinforcement construction. A mechanical model of roadway excavation was constructed to analyze the influences of excavation spatial effect on the stress releasing and bearing structure of surrounding rocks. A rock postpeak strain softening and dilatation model was introduced to investigate the mechanical characteristics of the surrounding rock mass in the rupture residual zone and plastic softening zone in a roadway. Moreover, we analyzed the influences of unloading and reinforcement construction on the stress path and mechanical characteristics of the rock unit model, which disclosed the adjustment mechanism of the bearing structure of surrounding rocks by the failure development status of rocks. A numerical simulation on the distribution of surrounding rock stress fields and adjustment features of the bearing structure after roadway excavation and unloading and reinforcement construction was carried out by using the FLAC 3D program. Results demonstrate that the unloading construction optimizes the axial ratio of spatial excavation in a roadway and the reinforcement zones on both sides are the supporting zones of the bearing structure. Moreover, the ratio between the distance from two side peaks to the roadway sides and the distance from the roof and floor peaks to the excavation space is equal to the coefficient of horizontal pressure. In other words, the final collapse failure mode of surrounding rock is that the long axis of the excavation unloading space points to the same direction with the maximum principal stress of the primary rock. Reinforcement forces the surrounding rocks to form a "Ω-shaped" bearing structure, which is in favor of the long-term maintenance of the roadway.